(untitled) - Yoshino, M. Y. (Boston, Mass., 1995)
Looks at the benefits of business alliances, discusses actual cases, and offers advice on managing strategic alliances and networks.
Keywords: Liên minh chiến lược (Kinh doanh),Strategic alliances (Business)